Chemical durability of alumina and selected glasses in simulated body fluid - Effect of composition and surface abrasion - Bengisu, M; Yilmaz, E (Kluwer Academic/Plenum Publ, 2004)
[Abstract Not Available]
10th International Symposium on Biomedical Science and Technology -- OCT 10-12, 2003 -- CYPRUS
Keywords: Bioactive Glass; In-Vitro; Bioceramics; S53P4